Core Material Manufacturing Study On Aluminum Composite Panel (ACP) - Fahruddin, A'rasy; Mulyadi, Mulyadi; Hardy Sujiatanti, Septia; Eryandrie Wicaksono, Majdi; Bamban Jakaria, Ribangun; Harmi Tjahjanti, Prantasi Harmi Tjahjanti (Ann Publisher, 2024)
An aluminum composite panel (ACP) is a flat panel with aluminum plates/sheets that are rigid and strong but relatively lightweight. Between the two plates, the core material content is generally made of polyethylene and polyurethane. However, the two core materials are not resistant to high temperatures/heat. They are flammable, so it is urgent to make variations of other core materials resistant to high temperatures. This study aims to provide variations for ACP core materials using polymer materials resistant to high temperatures, namely Low-Density polyethylene (LDPE) and Polyoxymethylene (POM). The method used is experimental/fabrication of ACP making. The high-temperature test was carried out in a furnace with a temperature of 3000C, 3500C, and 4000C, each with a holding time of 1 hour. The results obtained from observing the microstructure using an Optical Microscope before and after the test damaged the core material while the Aluminum metal was still intact. The mass of ACP before and after testing also changed. Overall, at the three temperatures above, the LDPE core material does not withstand this temperature because the temperature is above the melting point of the LDPE material.